2017
DOI: 10.1007/s11096-017-0552-1
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects of direct acting antiviral-based regimens in chronic hepatitis C patients: a Brazilian experience

Abstract: Background Direct-acting antivirals (DAA) are currently used for the treatment of chronic hepatitis C (HCV). However, few studies describe the adverse effects (AE) associated with DAA therapy in "real-word" cohorts. Aim To evaluate AE in Brazilian chronic HCV patients after DAA-therapy. Setting A reference center for hepatitis treatment in Rio de Janeiro, Brazil. Methods An observational "real-world" study was conducted with 102 chronic HCV patients undergoing DAA therapy for 12 or 24 weeks. The self-reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
2
3

Year Published

2018
2018
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 25 publications
0
12
2
3
Order By: Relevance
“…Besides, a previous study from our group described that one patient had SOF therapy discontinued due to hepatorenal syndrome. 17 Concerning the laboratory evaluation before and after treatment, we observed an improvement in hepatic parameters in both groups, as demonstrated by reduction in serum levels of ALT, AST, GGT and ALP, besides an increase in serum levels of albumin (Appendix S1).…”
Section: Re Sultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Besides, a previous study from our group described that one patient had SOF therapy discontinued due to hepatorenal syndrome. 17 Concerning the laboratory evaluation before and after treatment, we observed an improvement in hepatic parameters in both groups, as demonstrated by reduction in serum levels of ALT, AST, GGT and ALP, besides an increase in serum levels of albumin (Appendix S1).…”
Section: Re Sultsmentioning
confidence: 76%
“…The analysis of clinical data from patient's records showed that three patients (3.2%) from the GFR <45 mL/min/1.73 m 2 group had SOF daily doses adjusted due to an increase in Cr serum levels, and one patient (1.1%) had the treatment period reduced from 24 to 12 weeks for the same reason. Besides, a previous study from our group described that one patient had SOF therapy discontinued due to hepatorenal syndrome …”
Section: Resultsmentioning
confidence: 97%
“…[9][10][11] However, few studies have been conducted in Brazil evaluating the safety of direct-acting antivirals. 12,13 Thus this study aimed to identify factors associated with the development of adverse drug reactions (ADRs) to new direct-acting antiviral agents for hepatitis C treatment associated or not to ribavirin at three centers in the Brazilian public health system.…”
Section: Introductionmentioning
confidence: 99%
“…The present study was motivated by the limited availability of Brazilian research documenting and recording real-life data regarding the success rates of DAAs (12)(13)(14) . Here we evaluated the epidemiological profile of patients with chronic hepatitis C and the rate of SVR of all individuals treated in accordance to the Clinical Protocol and Therapeutic Guidelines of 2015 that attended the Reference Center for the treatment of chronic hepatitis C of the Federal University of Rio Grande, termed Center for the Application and Monitoring of Injectable Medicines (CAMMI).…”
mentioning
confidence: 99%